Access to medicines for rare diseases: A European regulatory roadmap for academia - Rosenberg, Noa; van den Berg, Sibren; Stolwijk, Nina N.; Jacobs, Bart A. W.; Post, Hendrika C.; Pasmooij, Anna M. G.; de Visser, Saco J.; Hollak, Carla E. M. (Frontiers in Pharmacology, 2023)
Background: Novel or repurposed medicines for rare diseases often emerge from fundamental research or empirical findings in academia. However, researchers may be insufficiently aware of the possibilities and requirements to bring novel medicinal treatment options to the patient. This paper aims to provide an easily applicable, comprehensive roadmap designed for academic researchers to make medicines for rare diseases available for patients by addressing the relevant regulatory frameworks, including marketing authorization and alternative routes. Methods: Key points of the regulatory chapters “Placing on the Market” and “Scope” of Directive 2001/83/EC relating to medicinal products for human use were summarized. Provisions in EU directives regarding blood products, radiopharmaceuticals, and herbal and homeopathic medicinal products were excluded. Cross-referencing to other provisions was included. European case-law was retrieved from the InfoCuria database to exemplify the implications of alternative routes. Results: Medicines may only be placed on the market with a valid marketing authorization. To obtain such authorization in Europe, a “Common Technical Document” comprising reports on quality and non-clinical and clinical studies must be submitted to a “competent authority”, a national medicine agency or the European Medicines Agency. Timely interaction of academic researchers with regulators via scientific advice may lead to better regulatory alignment and subsequently a higher chance for approval of academic inventions. Furthermore, reimbursement by national payers could be essential to ensure patient access. Apart from the marketing authorization route, we identified multiple alternative routes to provide (early) access. These include off-label use, named-patient basis, compassionate use, pharmacy compounding, and hospital exemption for Advanced Therapy Medicinal Products. Discussion: Aligning academic (non-)clinical studies on rare diseases with regulatory and reimbursement requirements may facilitate fast and affordable access. Several alternative routes exist to provide (early) pharmaceutical care at a national level, but case-law demonstrates that alternative routes should be interpreted strictly and for exceptional situations only. Academics should be aware of these routes and their requirements to improve access to medicines for rare diseases.